The Effect Of Time Variation Of Urine Glucose Level Testing On Patients With Diabetes Mellitus At Dolok Sanggul Regional Public Hospital - Zulkifli Simanjuntak; Renny Sihite (Jurnal EduHealth, 2025)
The Effect of Variation in Examination Time on Urine Glucose Levels at Dolok sanggul Regional General Hospital, Humbang Hasundutan Regency. Urinalysis is the most frequently performed examination. Urinalysis examination should be performed <1 hour after sampling. However, often with the large number of urine samples that must be examined and other conditions that cause the examination to be delayed. From previous studies, delayed urinalysis examination did not result in changes in urine sugar results. This study aims to determine the effect of delayed urine sample examination time on urine glucose examination results. This type of research is an experimental laboratory with chemical urinalysis examination for urine glucose examination, with a total of 39 samples carried out on April 1, 2023 - April 31, 2023 at the Dolok sanggul Regional General Hospital Laboratory, Humbang Hasundutan Regency. The results of statistical tests from this study showed no effect of the length of delay on urine glucose parameters. It can be concluded that there is no effect of delayed urine sample examination time on urine glucose examination results at Dolok sanggul Regional General Hospital.